# When a two digit number is added to its reverse, the result is 143. The number is 3 less than the sum of the squares of its digits. Calculate this number.

by kinzo 07.04.2015

number is 94.

Log in to add a comment

by kinzo 07.04.2015

number is 94.

Log in to add a comment

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

Let the number be N = a b where b is the units digit. a = the tens digit.

the value of the number* N = 10 * a + b*

number after reversing : b a

the value of the number* after reversing : 10 * b + a *

sum of the two numbers = 10 a + b + 10 b + a = 11 (a + b)

given, 11 ( a + b) = 143 =>* a + b = 13 *--- (1)

sum of squares of digits =* a² + b² = (a+b)² - 2 a b*

given,* N = 10 a + b = (a² + b²) - 3*

=> 10 a + b = (13² - 2 a b) - 3 = 166 - 2 a b

Hence,* 10 a + b + 2 a b = 166 * --- (2)

do (2) - 10 * (1) : - 9 b + 2 a b = 36

so* b (2a -9) = 36 --- (4)* .

substitute value of b from (1) in (4) :

(13 - a) ( 2a - 9) = 36

=> -2 a² + 35 a - 117 = 36

=> 2 a² - 35 a + 153 = 0

discr: 35² - 8 * 153 = 1

a = (35 +- 1)/ 4 = 9 or 8.5

we take the integer value only as a and b are integers less than 10.

* so a = 9 and b = 4 *

so the number is 94.

the value of the number

number after reversing : b a

the value of the number

sum of the two numbers = 10 a + b + 10 b + a = 11 (a + b)

given, 11 ( a + b) = 143 =>

sum of squares of digits =

given,

=> 10 a + b = (13² - 2 a b) - 3 = 166 - 2 a b

Hence,

do (2) - 10 * (1) : - 9 b + 2 a b = 36

so

substitute value of b from (1) in (4) :

(13 - a) ( 2a - 9) = 36

=> -2 a² + 35 a - 117 = 36

=> 2 a² - 35 a + 153 = 0

discr: 35² - 8 * 153 = 1

a = (35 +- 1)/ 4 = 9 or 8.5

we take the integer value only as a and b are integers less than 10.

so the number is 94.

the no. will be 10x+y

according to the question,,10x+y + 10y+x=143

11x+11y=143

by solving we get x+y=13

y=x-13 ..............eq 1

according to the question,,10x+y+3=x²+y² ............................eq 2

substituting eq 1 in eq 2

10x+13-x+3=x²+(13-x)²

by solving we get 2x²-35x+153=0

Solving the quadratic equation

a=2 b=-35 c=153

determinant=b²-4ac

=1225-1224

=1

√D =1

x=-b+√D÷2a or x=-b-√D÷2a

x=9 or x=34/4(ruled out since digits cannot

be fractions)

hence x=9

y=13-9

=4

the number is 94.

hope this helps u...